Comparison of Legal Protection of Labor in Indonesia and Pakistan - Alfani, M Iram; Sunarno, Sunarno (Jurnal Suara Hukum, 2024)
This article aims to conduct a comparative review of legal protections for workers in Indonesia and Pakistan, focusing on workers' rights and the sanctions imposed on companies that infringe upon these rights. The research serves to provide educational resources on labor protections for students and workers alike. Employing normative legal research methodology, both secondary and primary data were collected, with secondary data primarily sourced from literature reviews. Qualitative data analysis methods were applied to interpret information gathered from personal and official documents, as well as written sources, to derive conclusions. The findings highlight both similarities and differences in the implementation of workers' rights protections between Indonesia and Pakistan. Despite variations in approach, both countries demonstrate a commitment to upholding workers' rights within their respective legal frameworks. This study contributes to a deeper understanding of labor protections in diverse national contexts, offering valuable insights for academic study and practical application in the field of labor law and policy.